PERBANDINGAN TINGKAT AKURASI FORECASTING SAMBEL PECEL DENGAN METODE DOUBLE MOVING AVERAGE DAN DOUBLE EXPONENTIAL SMOOTHING - Suwignyo, Fahrul Afiyas; Suseno, Pangki (Universitas Multimedia Nusantara, 2025)
Abstract- Cihayu pecel sauce is an instant processed chili sauce made from the main ingredients, namely cayenne pepper, peanuts, garlic, brown sugar, salt, and lime leaves. These ingredients are ground and mixed into a paste which is served as a complementary sauce for vegetable pecel dishes. The purpose of this study was to forecast the demand for Cihayu pecel sauce for 2025, while comparing 2 methods to obtain the best sales forecast results for Cihayu pecel sauce. The methods used in forecasting the demand for Cihayu pecel sauce are the Double Moving Average and Double Exponential Smoothing methods using time series data. Based on the tests that have been carried out, it was found that the Double Moving Average (DMA) method with 4-period parameters is the method that is used effectively with a MAD of 2.91, an MSE of 16.37 and a MAPE of 0.84%. This means that the DMA model with 4 parameters is the best model for forecasting the amount of sales at Cihayu pecel sauce MSMEs in Mirigambar Village. Keywords: Forecasting; Double Moving Average; Double Exponential Smoothing; Time Series Analysis; MSME